Fenomena Fidget Spinner Ditinjau dari Sudut Pandang Konsumerisme dan Kultivasi Media dengan Pendekatan Analisis Konten - Alfirahmi Alfirahmi; Hafizh Faikar A. R. (LUGAS Jurnal Komunikasi, 2018)
The development of technology and information ultimately makes the flow of information exist in the absence of space and time or it is known as globalization.  Information flow is spread easily and everyone can access any information without limitations. That phenomenon ultimately creates new models, trends, or new products to meet the growing needs of society. Trends or models that are developed in society through social media make consumers view advertisement easily as well as make them consumptive. One example of a consumptive culture is the presence of a spinner fidget toy.  Fidget has been developing and getting great attention through the growing number of enthusiasts, and it is considered as a solution that can answer the needs of autism consumers. In addition, the development of spinner fidget toys is supported by the pattern of dissemination through social media that indirectly raises the buyer's interest in spinner fidget. Spinner fidget toy is only one of the few cases on how the purchasing power of society is limited to pleasure, and overriding the useful value of purchased goods. The unconscious community has the potential to become consumptive, and it affects mental development of the consumer level, and reduces the productivity of society. The purpose of this study is to analyze how the phenomenon of fidget spinner is viewed from the point of consumerism view and media cultivation with content analysis approach.